Kebijakan Penegakan Hukum Pidana dalam Menanggulangi Perjudian - Ida Arodatul Jannah; Sutopo (JOSH: Journal of Sharia, 2024)
Criminal law is often used to solve social problems, especially in crime prevention. In particular, the problem of gambling as a form of social disease, a form of social pathology. Enforcement of criminal law to tackle gambling as deviant behavior must continue to be carried out. This is very reasonable because gambling is a threat a real threat to social norms that can lead to individual tensions as well as social tensions. Gambling is a real or potential threat to the nation. Thus gambling can become an obstacle to national development with material-spiritual aspects. Because gambling educates people to make a living in an unreasonable manner and forming a "lazy" character. While development requires individuals who are active, hard working and mentally strong. It is very reasonable then gambling must immediately find ways and rational solutions for a solution. Because it is clear that gambling is a social problem that can interfere with the social functions of society. One of the rational efforts used to tackle gambling is the criminal law policy approach.The use of legal remedies, including criminal law, as an effort to overcome social problems, including in the field of law enforcement policies. Besides that, because the goal is to achieve public welfare in general, law enforcement policies are also included in the field of social policy, namely all rational efforts to achieve public welfare.